Sex-related differences in experimental pain sensitivity in subjects with painful or painless neuropathy after surgical repair of traumatic nerve injuries - Miclescu, Adriana Ana; Gkatziani, Panagiota; Granlund, Pontus; Butler, Stephen; Gordh, Torsten (Pain reports, 2022)
Sex-related influences represent a contributor to greater pain sensitivity and have a higher prevalence of many chronic pain conditions, including neuropathic pain (NP), among women.IntroductionSex-related influences represent a contributor to greater pain sensitivity and have a higher prevalence of many chronic pain conditions, including neuropathic pain (NP), among women.The aim was to analyze how differences in ongoing pain, experimental pain intensity, and conditioned pain modulation (CPM) relate to sex in subjects with neuropathy after traumatic nerve injuries.ObjectivesThe aim was to analyze how differences in ongoing pain, experimental pain intensity, and conditioned pain modulation (CPM) relate to sex in subjects with neuropathy after traumatic nerve injuries.Endogenous pain modulation was compared between male (n = 77) and female (n = 55) subjects and between subjects with NP (female = 31, male = 39) and pain-free subjects with posttraumatic neuropathy (female = 24, male = 38). Conditioned pain modulation was assessed by pain ratings to pressure stimuli before and after a noxious conditioning stimulus (CS) conducted with one arm submerged in cold water (4°C) for 1 minute. Time of recovery (Time off) of pain intensity from peak VASmaxc after CS was recorded and compared between male and female patients.MethodsEndogenous pain modulation was compared between male (n = 77) and female (n = 55) subjects and between subjects with NP (female = 31, male = 39) and pain-free subjects with posttraumatic neuropathy (female = 24, male = 38). Conditioned pain modulation was assessed by pain ratings to pressure stimuli before and after a noxious conditioning stimulus (CS) conducted with one arm submerged in cold water (4°C) for 1 minute. Time of recovery (Time off) of pain intensity from peak VASmaxc after CS was recorded and compared between male and female patients.Greater ongoing pain intensity was found among female patients compared with male patients and more experimental pain after pressure and cold induced pain. Summing all groups together, women had 0.8 times higher odds (20%) of recovering sooner than men after CS (95% CI = 0.65-2.9). No differences in CPM, time off, and psychosocial variables were seen between female and male patients (P < 0.05).ResultsGreater ongoing pain intensity was found among female patients compared with male patients and more experimental pain after pressure and cold induced pain. Summing all groups together, women had 0.8 times higher odds (20%) of recovering sooner than men after CS (95% CI = 0.65-2.9). No differences in CPM, time off, and psychosocial variables were seen between female and male patients (P < 0.05).Our hypothesis for sex differences in endogenous pain modulation was only supported by a shorter after-sensation time after cold CS in female patients. No sex differences in the magnitude of CPM effect were identified. Increased pain intensity for experimental pain, in both neuropathic pain and neuropathy without pain, was found in female patients.ConclusionOur hypothesis for sex differences in endogenous pain modulation was only supported by a shorter after-sensation time after cold CS in female patients. No sex differences in the magnitude of CPM effect were identified. Increased pain intensity for experimental pain, in both neuropathic pain and neuropathy without pain, was found in female patients.